2021
DOI: 10.1021/acschemneuro.1c00224
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Attenuates Cancer-Induced Bone Pain via NF-κB/CXCL12 Signaling in Midbrain Periaqueductal Gray

Abstract: Electroacupuncture (EA) is effective in various chronic pains. NF-κB and CXCL12 modulate the formation of chronic pain. Herein, we hypothesized that EA alleviates cancer-induced bone pain (CIBP) through NF-κB/CXCL12 axis in midbrain periaqueductal gray (PAG), which participates in “top-down” pain modulatory circuits. In order to filter the optimum EA frequency for CIBP treatment, 2, 100, or 2/100 Hz EA was set up. In addition, ipsilateral, contralateral, and bilateral EA groups were established to affirm the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
(103 reference statements)
0
15
0
Order By: Relevance
“…Finally, 18 studies were included in this review. 17-34 The literature selection process is detailed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 18 studies were included in this review. 17-34 The literature selection process is detailed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Nociceptive neurons located in laminae VII and VIII of the spinal cord and laminae V and VI of the SpV project to the PAG ( Mouton and Holstege, 2000 , Vanderhorst et al, 1996 ), posterior hypothalamic nucleus ( Çavdar et al, 2001 ), and intralaminar thalamic nuclei ( Carstens and Trevino, 1978 , Royce et al, 1991 , Shigenaga et al, 1983 ). The PAG-involved pain matrix has also been reported in all pain types, such as neuropathic pain ( Samineni, et al, 2017 ), inflammatory pain ( Li and Sheets, 2018 ), and cancer-induced bone pain ( Xu, et al, 2021 ). In a recent study, dopamine neurons in the ventrolateral periaqueductal gray/dorsal raphe (vlPAG/DR) through projections to the bed nucleus of the stria terminalis (BNST) contributed to sex differences in regulating pain-related behaviors ( Yu, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Pain Research 2023:16 998 chronic pain in these patients. 107 The underlying mechanism of cancer-induced bone pain includes reducing the expression of CXCL12 by inhibiting the activation of NF-κB, 108 suppressing the expression of 5-HT and 5-HT3AR, and increasing the expression of MOR and endomorphin-1 in the RVM-spinal cord pathway. 109 Recently, animal research revealed mTOR as a potential target in bone cancer pain and electroacupuncture analgesia.…”
Section: Dovepressmentioning
confidence: 99%